Nutrition and Carcinogenesis: An Exploratory Analysis - Chauhan, Kavita; Singal, Kabir; Syed, Asmara; Agarwal, Anshoo; Hussain Shah, Syed Sajid; Chatha, Wajid Ali; Syed, Inshrah; Syed, Fariha; Elmorsy, Ekramy M; Salama, Basem (Journal of Neonatal Surgery, 2025)
Background: Cancer cases around the world are increasing with every passing day. Cancers are caused by mutations in the four main groups of genes which are associated with the growth and development of cells. Chemical substances, physical agents and some microbes are associated with the causation of these mutations. Some diets contain such chemicals which could lead to the gene mutation resulting in the development of cancers. Awareness of such dietary factors among the community could be helpful in the prevention of cancers. Material and Methods: Research papers were collected from the different databases by searching the key words such as cancers, malignant tumors, malignancies, diet, dietary patterns, dietary factors, carcinogenesis, food, edibles. Searched databases included PubMed, Google scholar, Scopus and Web of Science. After reviewing the titles and abstracts, a total of sixty-seven research articles were selected for this review paper. Results: The collected research papers were reviewed by the nominated group of authors. A significant number of papers revealed that the certain diets are associated with some types of cancers. The important categories of cancer associated with the dietary factors include colorectal cancer, gastric carcinoma, esophageal cancers, malignant tumors of oral cavity, breast carcinoma, cancers of lung and pancreatic carcinoma. The diets associated with cancers include increased intake of processed meat, sulfur microbial diet, industrially processed food, pro-inflammatory diet and reduced intake of fiber, fruits & vegetables. Conclusion: Many cancers have been associated with the unhealthy food. One of the important strategies for the reduction in the morbidity and mortality due to cancer is to find out the potential preventable risk factors of cancers. The adaption of healthy diet could be very vital in the reduction of cancer incidence.